2020
DOI: 10.1007/s11858-020-01142-0
|View full text |Cite
|
Sign up to set email alerts
|

Effective design of massive open online courses for mathematics teachers to support their professional learning

Abstract: Three MOOCs for Educators (MOOC-Eds) were designed for mathematics and statistics teachers based on principles of effective online professional development that include: self-directed learning, learning from multiple voices, job-connected learning, and peer-supported learning (Kleiman et al., in: Kim (ed) Massive Open Online Courses: the MOOC Revolution, Routledge, New York, 2015). We examined how these design principles were enacted in the development of the MOOC-Eds and how they influenced the engagement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 30 publications
0
14
0
3
Order By: Relevance
“…Online teaching, both synchronous and asynchronous, is not new, and there already exists a growing body of literature on this issue (e.g., Engelbrecht, & Harding, 2005;Hollebrands, & Lee, 2020;Joubert, 2013;Juan, Steegmann, Huertas, Jesus Martinez, & Simosa, 2011). Despite several differences between face to face and online education, previous studies (e.g., Engelbrecht & Harding, 2005;Joubert, 2013) highlighted that the basic principles of teaching and learning of mathematics should follow in an online environment; such as having a sound balance between teacher and learner-centred activities and creating opportunities for students to develop a relational understanding of mathematics, or from the commognitive perspective, making their transition from ritualised to explorative discourse.…”
Section: Online Teaching and Learning Of Mathematicsmentioning
confidence: 99%
“…Online teaching, both synchronous and asynchronous, is not new, and there already exists a growing body of literature on this issue (e.g., Engelbrecht, & Harding, 2005;Hollebrands, & Lee, 2020;Joubert, 2013;Juan, Steegmann, Huertas, Jesus Martinez, & Simosa, 2011). Despite several differences between face to face and online education, previous studies (e.g., Engelbrecht & Harding, 2005;Joubert, 2013) highlighted that the basic principles of teaching and learning of mathematics should follow in an online environment; such as having a sound balance between teacher and learner-centred activities and creating opportunities for students to develop a relational understanding of mathematics, or from the commognitive perspective, making their transition from ritualised to explorative discourse.…”
Section: Online Teaching and Learning Of Mathematicsmentioning
confidence: 99%
“…In response to the general objective of this research, it was found that personal factors [3,4], family factors [8][9][10], social factors [14], instructional design factors [17,18] and labor factors [29] influence both the decision to take a MOOC (expectation-value) and, to a certain extent, engagement in the training program-measured by completion rates-as noted in the review of the state of the art. However, not all factors do so in the same way.…”
Section: Discussionmentioning
confidence: 96%
“…Labor considerations are also essential elements for engagement in MOOCs. Research on Massive Online Open Courses finds that one way to keep participants involved in training activities is to offer a certificate of completion for a fee, increasing student engagement by 10-12% [26,27], teacher reputations [28], and the development of new skills that will be useful in their work or studies [29].…”
Section: Introductionmentioning
confidence: 99%
“…The relevance aspect of the ARCS model refers to how the topic or the manner in which the material is taught is relevant to learners’ needs and experience [ 11 ]. The high relevance of VFD in effectively addressing faculty knowledge and skill gaps, and the need to connect contributed to the initial success [ 19 21 ]. The quick transition to virtual learning while physically distancing made faculty acutely need to learn about virtual teaching, while also offering connection to colleagues at a challenging time.…”
Section: Applying the Lenses Of Disruptive Innovation And The Arcs Fr...mentioning
confidence: 99%